2018
DOI: 10.1097/ncc.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Using Social Media for Cancer Prevention and Management

Abstract: Social media use in cancer care will facilitate improved communication and support among patients, caregivers, and clinicians and, ultimately, improved patient care. Clinicians need to carefully harness social media to enhance patient care and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 33 publications
0
55
0
1
Order By: Relevance
“…However, these benefits and the diffuse and widely distributed nature of social media means that it is likely that more than the usual research techniques are required to capture its impact for public health good and cancer education at a population level. Further research is required to investigate the use and impact of social media interventions (delivered through Facebook, YouTube and other channels) in terms of delivering effective education and improving cancer awareness [26]. Regarding the helpline, there do not appear to be any studies that report the use of a helpline and its uptake as part of a cancer awareness campaign.…”
Section: Discussionmentioning
confidence: 99%
“…However, these benefits and the diffuse and widely distributed nature of social media means that it is likely that more than the usual research techniques are required to capture its impact for public health good and cancer education at a population level. Further research is required to investigate the use and impact of social media interventions (delivered through Facebook, YouTube and other channels) in terms of delivering effective education and improving cancer awareness [26]. Regarding the helpline, there do not appear to be any studies that report the use of a helpline and its uptake as part of a cancer awareness campaign.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Similarly, some literature reviews reported the extensive use of Twitter, Facebook, mobile phones, and other social media and mhealth technologies for the education, prevention, treatment, and management of cancer. 22 25 Another study investigated the use of mobile phones to increase knowledge about cancer. 26 In addition, a recently published book presents an extensive analysis of the fundamentals and applications of mHealth technologies, including the management of chronic diseases such as cancer, among others.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is the NHS “Open for business” campaign run by Public Health England earlier this year. (22) Social media has the potential to be effective in cancer prevention (23) and could be employed for public health messaging, particularly for younger adults. Communication directed at older age groups could comprise more traditional media channels, but given the unique challenges regarding health communication globally in 2020, (24) the optimal mode of campaigning remains to be determined.…”
Section: Discussionmentioning
confidence: 99%